Pengaruh Etika Kerja, Profesionalisme Kerja, Dan Disiplin Kerja Terhadap Kinerja Pegawai - Putri Wahyu Ningsih; Hadi Sunaryo; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine whether work ethics, work professionalism, and work discipline partially and simultaneously affect employee performance at the Lowokwaru District Office, Malang City. The sampling technique used a saturated sample with a total sample of 34 employees. The type of research used is explanatory research. The data analysis method in this study used descriptive and  inferential statistical analysis using the SPSS program. The results showed that simultaneously the independent variables had a significant effect on the dependent variable. Based on the partial test results, the variables of work ethics, work professionalism and work discipline have a significant effect on the performance of the employees of the Lowokwaru District Office, Malang City. The contribution of this research can be an evaluation of employee performance on factors of work ethics, work professionalism, and work discipline as a reference for employee performance and provide input to the government regarding the improvement of ASN at the Lowokwaru District Office, Malang City. Keywords: Work Ethics, Work Professionalism, Work Discipline and Employee Performance